Upaya Penurunan Suhu Tubuh Pada Anak Dengan Typhoid - Pebrianto, Arief, Irdawati, S.Kep.,Ns.,M.Si.,Med, Dian Nur Wulan Ningrum, S.Kep.,Ns.,M.Kep (2017)
Typhoid fever is a systemic infection caused by salmonella typhi in the surrounding neighborhood. Typi salmonalla disease can be transmitted through food consumption less intact his hygiene or contaminated water. Symptoms appear in typhoid fever are nausea, vomiting, and fever. If an increase in body temperature. So feared berakibatkan such fatal convulsions in children. The authors will act with nursing care for the patient's body temperature hipertermidengan measures to provide a warm compress. By giving a warm compress technique impending fasedilatasi in blood vessels and facilitate evaporation of the patient's body temperature will be normal. Interventions followed by teaching do warm compresses to the mother of the patient, so that the patient's mother could perform independently.